THE IMPORTANCE OF PLAY IN THE MENTAL DEVELOPMENT OF A CHILD - Soliyev Ilhomjon Sobirovich; Axmedova Turg’unoy Sultonali qizi (Galaxy International Interdisciplinary Research Journal, 2024)
Play is a fundamental aspect of childhood that plays a critical role in the mental development of children. This article explores the multifaceted benefits of play, drawing on extensive research from psychology, education, neuroscience, and pediatrics. It examines how play contributes to cognitive development by enhancing memory, attention, and problem-solving skills, and how it fosters social development through improved communication, cooperation, and empathy. Emotionally, play provides a safe outlet for children to express and regulate their emotions, promoting resilience and psychological well-being. The review also highlights neuroscientific findings that demonstrate play’s positive impact on brain development. Furthermore, the article discusses the implications for parents, educators, and policymakers in fostering environments that support and encourage play. Recognizing and preserving the value of play is essential for the holistic development of children, ensuring they grow into well-rounded, healthy, and capable individuals. This exploration underscores the irreplaceable value of play in nurturing a healthy and resilient future generation.